2003
DOI: 10.1097/00124645-200309000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Setting Valid Cut-Off Scores for Competency

Abstract: Results of competency, or certification, tests can have serious consequences for individuals tested, for employers, and for the public. However, the validity of testing outcomes depends not only on the validity of the test's content but also on the validity of the score selected as the passing, or cut-off, score. This article describes procedures and techniques for use by staff development professionals to ensure systematic, rational, and defensible cut-off scores for competency tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Cutoff scores for competency should never be selected in an arbitrary manner. 22 The authors found that nurses with certification, especially wound care certification, scored significantly higher on the PZ-PUKT than did nurses lacking clinical certification. This adds to the test's validity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cutoff scores for competency should never be selected in an arbitrary manner. 22 The authors found that nurses with certification, especially wound care certification, scored significantly higher on the PZ-PUKT than did nurses lacking clinical certification. This adds to the test's validity.…”
Section: Discussionmentioning
confidence: 97%
“…Setting a high cutoff score reduces the possibility of saying a person is competent when the person is not, thus having deleterious consequences. 22 Setting a score too high may mean loss of valuable resources if a person must retake a class or program. Researchers and educators need to examine various methods of cutoff score determination and select the method that fits best; thus, cutoff scores may vary by setting or the level of expertise, such as wound care certification.…”
Section: Discussionmentioning
confidence: 99%
“…In order to translate the NOP-CET scores into clinically meaningful units, however, it is necessary to decide on cut-off points for what is clinically sound competence. In this light, Azzarello (2003) emphasises the importance of making a rational and defensible cut-off point between competent and incompetent. The goal is to have as few misclassifications, either false positives or false negatives, as possible.…”
Section: Methodological Choicesmentioning
confidence: 99%
“…Scores from the NOP-CET can also be used in an evaluative manner by establishing the lowest clinically acceptable score or by giving demerit points to respondents that give answers that are clinically harmful. However, this requires further research, as it is important to make rational and defensible cutoffs between competent and incompetent, and the goal is to have as few misclassifications, either false positives or false negatives, as possible [181].…”
Section: Interpretabilitymentioning
confidence: 99%
See 1 more Smart Citation